Carrier density control in Cu2HgGeTe4 and discovery of Hg2GeTe4via phase boundary mapping. Issue 2 (13th December 2018) - Ortiz, Brenden R.; Gordiz, Kiarash; Gomes, Lídia C.; Braden, Tara; Adamczyk, Jesse M.; Qu, Jiaxing; Ertekin, Elif; Toberer, Eric S.
Abstract : Phase boundary mapping in Cu2 HgGeTe4 allows discovery of Hg2 GeTe4 and further enables carrier density control over 4 orders of magnitude. Abstract : The optimization and application of new functional materials depends critically on our ability to manipulate the charge carrier density. Despite predictions of good n-type thermoelectric performance in the quaternary telluride diamond-like semiconductors ( e.g. Cu2 HgGeTe4 ), our prior experimental survey indicates that the materials exhibit degenerate p-type carrier densities (>10 20 h + cm −3 ) and resist extrinsic n-type doping. In this work, we apply the technique of phase boundary mapping to the Cu2 HgGeTe4 system. We begin by creating the quaternary phase diagram through a mixture of literature meta-analysis and experimental synthesis, discovering a new material (Hg2 GeTe4 ) in the process. We subsequently find that Hg2 GeTe4 and Cu2 HgGeTe4 share a full solid solution. An unusual affinity for CuHg and HgCu formation within Cu2 HgGeTe4 leads to a relatively complex phase diagram, rich with off-stoichiometry. Through subsequent probing of the fourteen pertinent composition-invariant points formed by the single-phase region, we achieve carrier density control ranging from degenerate (>10 21 h + cm −3 ) to non-degenerate (<10 17 h + cm −3 ) via manipulation of native defect formation. Furthermore, this work extends the concept of phase boundary mapping into the realm of solid solutions and clearly demonstrates the efficacy of the technique as a powerful experimental tool within complex systems.